# Derivation using Ito's Lemma of price process

Define $q(t)$ as the log price minus a linear trend

$$q(t) = \ln P(t) - \mu t$$

Assume the log price process = Equation 1: $$dq(t) = - \Theta q(t) dt + \sigma dW(t)$$

Can you show that the solution to Equation 1 is: $$\ln P(t+h) - \ln P(t) = \mu h + (\exp(-h \Theta) - 1) \ln P(t) + \sigma \int_t^{t+h} \exp(-\Theta(t-u))dW_u$$

• Changed the term $\int^t_{t+h} \exp(-\Theta(t-u)dW_u)$ to $\int_t^{t+h} \exp(-\Theta(t-u))dW_u$, according to the original paper. – Gordon Nov 2 '15 at 16:07

by application of Ito's lemma , we have $$d\left(q(t)e^{\Theta\,t}\right)=\Theta \,q(t)e^{\Theta\,t}dt+e^{\Theta\,t}dq(t)+0$$ then $$d\left(q(t)e^{\Theta\,t}\right)=\sigma e^{\Theta\,t}dW_t$$ in other words $$q(t+h)e^{\Theta\,(t+h)}-q(t)e^{\Theta\,t}=\sigma\int_{t}^{t+h}e^{\Theta\,u}dW_u\Rightarrow$$ $$q(t+h)-q(t)=\left(e^{-h\Theta}-1\right)q(t)+\sigma\int_{t}^{t+h}e^{-\Theta\,(t+h-u)}dW_u$$ By substituting $\ln P(t)-\mu\,t$ to last equation , we have $$\ln P(t+h) -\ln P(t) =\mu h+\left(e^{-h\Theta}-1\right)(\ln P(t)-\mu t) + \sigma\int_{t}^{t+h}e^{-\Theta\,(t+h-u)}dW_u$$
• From EQ(1) we get $$\ln P(t) = q(t) + \mu t$$ Hence $$d \ln P(t) = dq(t) + \mu dt$$ Now put the solution for q into the equation and u'll get the result from the paper. – Phun Aug 1 '15 at 22:54